STRATEGI PENGEMBANGAN BISNIS PT. ALPINDO MITRA BAJA DENGAN MENGGUNAKAN ANALYTIC NETWORK PROCESS (ANP) - Marwansyah, Eko; Widyastuti, Sri; Tabroni (EKOBISMAN : JURNAL EKONOMI BISNIS MANAJEMEN, 2017)
The development of business strategy is an important aspect to achieve corporate goals. It requires accurate strategy planning in developing a company or business. This study was conducted on PT. Alpindo Mitra Baja (PT AMB), one of the steel plate manufacturer companies in West Java. The high challenge faced by the companies forced their top management to think harder in determining the strategies to be applied. The uncertain business climate and the recovering condition of the company were the factors that must be identified. This study used the SWOT analysis method which was developed by weighting over IFA (Internal Factor Analysis) and EFA (External Factor Analysis). It required an analytical technique to test the model and the relation generated by the SWOT. The analytical techniques used in this study was Analytic Network Process or ANP. The use of ANP analysis tools was also aimed to find the priority strategy. Using ANP, based on the weighted sequence of the largest, it can be seen that the sequence of strategies is "increase the working capital especially for new projects" by 1,0000000, "strengthen the HRD system to discipline employees" by 0,746776 "conduct employee competency training Amounting to 0,488718, "improving production quality" 0,244288, "creating SIM to expand foreign and domestic market of 0,153744" and implementing ISO-certified management system "of 0,097903.